(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This paper introduces a system dynamics model that integrates emerging technologies in the pursuit of sustainable agritourism development within communities. Based on Society 5.0, this model aims to blend technological innovations with community-oriented approaches so as to redefine the agritourism landscape. The suggested framework picturizes an integrated and harmonious relationship between agritourism, emergent technologies and societal dynamics for achieving a holistic and comprehensive development paradigm. Through exploiting the potentials of Society 5.0, the model hopes to increase community participation, promote sustainability practices and create enhanced overall experience in agritourism. With the synthesis of systems’ dynamic principles and philosophy of Society 5.0, this study contributes to discussing future directions for agritourism development that concentrate on community-based tourism with technology integration in its path towards future growth trajectory.